Dual Mechanisms of CYP3A Protein Regulation by Proinflammatory Cytokine Stimulation in Primary Hepatocyte Cultures - Lee, Choon-Myung (American Society for Pharmacology and Experimental Therapeutics, 2009)
Whereas many cytochrome P450 enzymes are transcriptionally suppressed by inflammatory stimuli, down-regulation of CYP2B protein by the inflammatory cytokine interleukin (IL)-1β is nitric oxide (NO)-dependent and occurs via polyubiquitination and proteasomal degradation. Here, we used iTRAQ proteomic analysis to search for other proteins that are potentially down-regulated by cellular NO in cultured rat hepatocytes, and we identified CYP3A1 as one such protein. Therefore, we examined whether CYP3A proteins, like CYP2B, undergo NO- and proteasome-dependent degradation in response to cytokine treatment of rat hepatocytes. In cultured rat hepatocytes treated with phenobarbital, IL-1β stimulation failed to down-regulate CYP3A1 mRNA within 24 h of treatment, whereas CYP3A protein was down-regulated to 40% of control within 6 h, showing the post-transcriptional down-regulation of CYP3A1 protein. The down-regulation of CYP3A after 9 h of stimulation by IL-1β was attenuated by inhibitors of NO synthase (NOS) and of the proteasome, showing NO- and proteasome-dependent down-regulation at earlier time points. However, the down-regulation of CYP3A evoked by IL-1β measured 24 h after stimulation was not affected by the inhibition of NOS or by proteasomal inhibitors, showing that CYP3A1 down-regulation at later time points is NO- and proteasome-independent. IL-6, which did not evoke NO production nor affect CYP3A1 mRNA within 24 h, produced a delayed proteasome-independent down-regulation as well. Taken together, these observations show a novel dual mode of post-transcriptional CYP3A down-regulation by cytokines: NO- and proteasome-dependent at earlier time points and NO- and proteasome-independent at later times.